Net Energy Analysis and Techno-Economic Assessment of Co-Production of Bioethanol and Biogas from Cellulosic Biomass - Teeraya Jarunglumlert; Chattip Prommuak (Fermentation, 2021)
Co-production is a process based on the biorefinery concept that maximizes the benefit of biomass by reusing residue from the production of one product to produce others. In this regard, biogas is one of the most researched second products for the production of ethanol from cellulosic biomass. However, operating this scheme requires additional investment in biogas processing equipment. This review compiles data from research studies on the co-production of bioethanol and biogas from lignocellulosic biomass to determine which is more worthwhile: leaving the residue or investing more to benefit from the second product. According to previous research, ethanol stillage can be converted to biogas via anaerobic digestion, increasing energy output by 2–3 fold. Techno-economic studies demonstrated that the co-production process reduces the minimum ethanol selling price to a level close to the market price of ethanol, implying the possibility of industrializing cellulosic ethanol production through this scheme.